The Role of Budgetary Planning in Improving Target Cost: A study on a sample of Saudi industrial companies operating in Jeddah (The International Journal for Scientific Research, 2025)
This study mainly aimed to reveal the role of planning budgets in improving the target cost. To achieve the study objectives, the researcher followed the descriptive analytical approach. A questionnaire was also used to collect primary data from the target sample of the study. The study population represented the employees of industrial companies listed in the Saudi Stock Exchange. The total study population size was (1119) employees, while the simple random sample size targeted by the study was (286) employees. Responses were obtained from (165) employees. The SPSS program was used. The study reached a number of results, represented by the presence of a statistically significant impact of the planning budget on the target cost. This is reinforced by the value of the coefficient of determination (R2 = 0.515), meaning that the use of the planning budget in industrial companies explains 51.5% of the change in the size of the target cost. The study recommended the necessity of using the planning budgets method as one of the modern administrative tools due to its effectiveness in improving performance and its impact on controlling product costs.
Keywords: Planning Budgets; Product Costs; Target Costing; Saudi Industrial Companies